The Role of Printed Media Regarding the Position of Woman in Albania - Hoxha, Isida (European Journal of Multidisciplinary Studies, 2016)
This paper analyzes the content of independent printed media regarding the woman position in Albania. Performing out its functions, media often reflects the stereotypes of the society; one of these stereotypes is the reflection of gender, especially woman. Even if media plays an important role in the process of socialization, it also has the obligation to transmit and make public a proper and good image of individuals. The most important function of media is that, while reflecting the society, it should not create or transmit stereotypes and should not play a role on their reinforcement. Related the gender stereotype and media role on this issue I have chosen the case study called Ajshe Vata. This case study is important because it represents the story of the murder of a young girl in Albania called Ajshe Vata. The importance of this case lays in the importance that media showed to this death. Therefore, the research question of this study is; what is the role of independent printed media in Albania in the cases when woman is the victim? Do the stereotypes created by society get reinforced by the printed media? Methodology used in this study will be discourse analyses in the printed media which at the same time will be the main theory of this paper. I will choose the independent newspapers during the period October 2012, when the case takes place